Video- assisted thoracoscopic lung resection with or without enhanced recovery after surgery: a single institution, prospective randomized controlled study - Ding, Yi; Zhou, Leiming; Shan, Lei; Zhang, Weiquan; Li, Peichao; Cong, Bo; Tian, Zhongxian; Zhao, Yunpeng; Zhao, Xiaogang (Frontiers in Oncology, 2024)
PurposeThis study was conducted to evaluate the postoperative short-term outcomes of patients undergoing video-assisted thoracoscopic surgery (VATS) for lung resection with the enhanced recovery after surgery (ERAS) protocol.MethodsA single-institution, prospective randomized controlled study was conducted. The primary outcome measures were postoperative pulmonary complications (PPCs) and postoperative short-term effects.ResultsAmong the 611 patients, 305 were assigned to the ERAS group, and 306 were assigned to the routine group. The ERAS group achieved earlier oral feeding, earlier mobilization, a shorter duration of drainage (2.0 vs. 5.0 days, P<0.001), and a shorter hospital stay (3.0 vs. 7.0 days, P<0.001). The biological impacts were confirmed to be significantly better for the ERAS group. Furthermore, the ERAS group also had a lower incidence of PPCs (11.5% vs. 22.9%, P<0.001) than did the routine group. Multivariate logistic regression analysis revealed the following predictors of drainage tube removal on the 1st day after surgery without pneumonia during hospitalization: comorbidity (P=0.029), surgical procedure (P=0.001), and operation time (P=0.039).ConclusionsImplementation of the ERAS protocol led to a decreased incidence of PPCs, suggesting that the ERAS protocol has a better biological impact on patients undergoing VATS for lung resection. Multigradient individual ERAS protocols are recommended at different institutions according to the individual conditions of patients.Clinical Trial Registrationhttps://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S0009ZT9&selectaction=Edit&uid=U0002ZGN&ts=3&cx=ks7hrg, identifier NCT04451473.